Radiographic Abnormalities in Barrel Racing Horses with Lameness Referable to the Metacarpophalangeal Joint - Menarim, Bruno Carvalho (2012)
Barrel racing is one of the most popular uses of the American Quarter horse in North and South America. Although injury to the metacarpophalangeal joint frequently occurs in this sport, there is limited information describing the nature of these injuries. The aim of this study was to determine the most common radiographic abnormalities in barrel racing horses with lameness referable to the metacarpophalangeal joint. lameness examinations were performed on 63 barrel racing horses. Those found to be lame were subjected to radiographic examination. Lameness at trot was scored on a scale of 0-5 (0 = sound; 5 = inability to move). Data were analyzed using descriptive statistical analysis. of horses examined, 30 (47.6%) were lame with scores ranging from 1 to 4. Half of the lame horses (15 of 30) had grade 2 lameness of the right forelimb. Abnormal radiographic findings were more often present on the left forelimb and included signs of sesamoiditis (70%), villonodular synovitis (56.6%), osteoarthritis (36.6%), osteochondritis dissecans (13.3%), capsulitis (13.3%), and soft-tissue swelling (6.6%). Radiographic abnormalities indicated that sesamoiditis, villonodular synovitis, and osteoarthritis may be associated to mild-to-moderate lameness in barrel racing horses. Complementary sonographic evaluation is recommended to better characterize soft-tissue abnormalities. (C) 2012 Elsevier B.V. All rights reserved.